UNIT 1.30 A Quantitative Method for Comparing the Brightness of Antibody‐dye Reagents and Estimating Antibodies Bound per Cell. Issue 1 (1st July 2016) - Kantor, Aaron B.; Moore, Wayne A.; Meehan, Stephen; Parks, David R.
Abstract : We present a quantitative method for comparing the brightness of antibody‐dye reagents and estimating antibodies bound per cell. The method is based on complementary binding of test and fill reagents to antibody capture microspheres. Several aliquots of antibody capture beads are stained with varying amounts of the test conjugate. The remaining binding sites on the beads are then filled with a second conjugate containing a different fluorophore. Finally, the fluorescence of the test conjugate compared to the fill conjugate is used to measure the relative brightness of the test conjugate. The fundamental assumption of the test‐fill method is that if it takes X molecules of one test antibody to lower the fill signal by Y units, it will take the same X molecules of any other test antibody to give the same effect. We apply a quadratic fit to evaluate the test‐fill signal relationship across different amounts of test reagent. If the fit is close to linear, we consider the test reagent to be suitable for quantitative evaluation of antibody binding. To calibrate the antibodies bound per bead, a PE conjugate with 1 PE molecule per antibody is used as a test reagent and the fluorescence scale is calibrated with Quantibrite PE beads. When the fluorescence per antibody molecule has been determined for a particular conjugate, that conjugate can be used for measurement of antibodies bound per cell. This provides comparisons of the brightness of different conjugates when conducted on an instrument whose statistical photoelectron (Spe) scales are known. © 2016 by John Wiley & Sons, Inc.